Legal Protection of Computer Programs - Abdul ameer, Ahmed (Journal of Legal Sciences, 2023)
Computer programs are one of the most prominent features of technical progress in the field of information technology, which has raised many new issues that have not existed since the mid-twentieth century. and controls on the use of these programs by third parties, Controversy still exists about the legal nature of computer programs between those who believe that they are subject to the laws of patents and industrial property, and those who believe that they are subject to the laws of copyright protection and literary and artistic property, and the resulting difference in the scope of protection and rights established according to the legal system adopted in the application. This study comes to shed light on the legal nature of computer programs and to indicate the legal conditions that are required to be covered by protection.